High heritability of speech and language impairments in 6-year-old twins demonstrated using parent and teacher report. - Bishop, D; Laws, G; Adams, C; Norbury, C (2006)
Previous twin studies have demonstrated high heritability of specific language impairment (SLI) when the diagnosis is based on psychometric testing. The current study measured the effectiveness of parent and teacher ratings of communication skills in identifying heritable language impairment. The Children's Communication Checklist was completed by parents and teachers of 6-year-old twins recruited from a general population sample. One hundred and thirty twin pairs (65 MZ) were selected because at least one twin had low language skills at 4 years of age; a further 66 pairs (37 MZ) were a low risk group with no indication of language difficulties at 4 years. Internal consistency, inter-rater reliability, and validity in identifying language impairment were assessed for all CCC scales. CCC scales, especially those assessing structural language skills, were highly effective in identifying cases of language impairment, but agreement between parent and teacher ratings was modest. Genetic analysis revealed negligible environmental influence and substantial genetic influence on most scales. A rater-specific effects model was fit to the data to assess how far parents and teachers assess a common genetic factor on the CCC. Ratings of parents and teachers were influenced to some extent by the same child characteristics, but rater-specific effects were also evident, especially on scales measuring pragmatic aspects of communication. This study shows that there are strong genetic influences on both structural and pragmatic language impairments in children, and these can be detected using a simple checklist completed by parents or teachers.